Pain sensitivity is associated with general attitudes towards pain: Development and validation of a new instrument for pain research and clinical application. (16th March 2022) - Vetterlein, Annabel; Monzel, Merlin; Richter‐Hetzer, Sandy; Kapala, Katharina; Geppert, Juliane; Baki, Sophia; Reuter, Martin
Abstract: Background: With regard to attitudes towards pain, many questionnaires have been developed. Although undoubtedly useful, they were specifically designed for the use in chronic pain and are less suitable for the assessment in the general population. The purpose of the present paper was to develop a measure for the assessment of general attitudes towards pain applicable in the general population, regardless of clinical condition, and to test its psychometric properties. Methods: We developed the General Attitudes Towards Pain Inventory and conducted two studies in order to provide psychometric data: In a general population sample ( N = 362, study one), participants were asked to complete a questionnaire battery. To assess test–retest reliability, participants were contacted again after 4 weeks (retest sample: N = 101). For the evaluation of criterion validity (study two), a sample with sadomasochistic sexual preference ( N = 68) was additionally recruited. Results: Statistical analyses revealed, overall, acceptable internal consistencies and test–retest reliabilities. A 10‐factor model showed acceptable fit and was superior to alternative models. The inventory demonstrated convergent and divergent validity. In this context, we found pain sensitivity to be associated with pain attitudes. Finally, compared to the general population sample, individuals with sadomasochistic sexual preference showed significantly higher scores on fascination ‐ pleasure and challenge subscales. Conclusions: In the present paper, we introduce a new and comprehensive instrument for pain research and provide evidence for its reliability and validity. In addition, we present new insights into how interindividual differences in pain sensitivity relate to pain attitudes. Statement of Significance: Acknowledging the lack of basic research on pain attitudes in the general population, we have developed and validated the first psychometric instrument to measure ten general attitudes towards pain. The inventory is based on the literature and clinical expertise and has been demonstrated to be useful in pain sensitivity research. In the clinical context, general pain attitudes could be pivotal when a person who has only known everyday pain suddenly becomes a patient confronted with prolonged states of intense pain.